‘I quit’ versus ‘I'm sorry I used’: A preliminary investigation of variations in narrative ending and transportation - Banerjee, Smita C. (Psychol Health, 2012)
A narrative experience can partly depend on how a narrative ends or concludes. This study examined prevention effects of personal drug use narratives varying by type of ending and gender of protagonist. Additionally, the role of transportation in the persuasion process, particularly the association between transportation and cocaine use intentions, both directly and indirectly, through the mediation of antidrug and pro-drug expectancies was assessed. A total of 500 undergraduate students at a large northern university in the UK participated in the experiment which was a 2 × 2 × 2 mixed design with ending (progressive vs. regressive) and gender of protagonist (male vs. female) as within-participants factors and participant gender (male vs. female) as between-participants factors. The results demonstrated significant main effects for ending, gender of protagonist in the narrative and participant gender, but no interaction effects. Finally, greater transportation was associated with stronger anti-cocaine expectancies, which were further associated with lower cocaine use intentions. Important theoretical and empirical implications are discussed.